Mechanical, vibration damping and acoustics characteristics of hybrid aloe vera /jute/polyester composites - S. Senthilrajan; N. Venkateshwaran; R. Giri; Sikiru O. Ismail; Rajini Nagarajan; Kumar Krishnan; Faruq Mohammad (Journal of Materials Research and Technology, 2024)
The development of biodegradable hybrid fibre composites is gaining pace in the automotive and construction industries due to their lightweight structural applications, which offer considerable benefits for the environment. In this present investigation, hybrid bio composites were fabricated using a compression molding machine with plain woven jute and aloe vera mats along with polyester resin as the matrix. Six types of hybrid biocomposite laminates were prepared by varying the stacking arrangement of jute and aloe-vera mats to analyse the impact of stacking arrangements on vibration damping and acoustic behaviour of these hybrid bio composites. From the results, it is concluded that the maximum value of natural frequency is obtained from the JJAJ type of composite. i.e., 157, 326, and 370 Hz for Modes I, II, and III respectively, due to good interlacing of fibres in the weft and warp directions. J/J/A/J (AJ3) hybrid bio composite has highest sound absorption coefficient of 0.47 at 3000 Hz, and a better transmission loss i.e 19.84 dB, according to the results of the acoustic research. The comparison of experimental and theoretical analysis was carried out, and found that experimental and theoretical values are closely related to each other.